The Most Select and the Most Democratic: A Century of Science in the Royal Society of Canada - Levere, Trevor (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1996)
ABSTRACTThis paper is a history of the Science Academy of the Royal Society of Canada, from its foundation in 1882 until the early 1990s. The RSC has always had an honorific role, but it has sought a more substantive one in science, in advising government, in scientific publication (a role that it has largely lost to the National Research Council and to other scientific societies and journals), in educating the public, in representing Canada internationally, and in undertaking scientific inquiries of public import, for example in assessing the risks associated with nuclear winter, or in the Canadian Global Change Program. Often, Fellows of the RSC have individually achieved more in science than the Society has achieved institutionally; but as this narrative shows, the dynamic between science, government, the RSC, and the Canadian public, has been important in Canadian science and in Canadian history.